2022
DOI: 10.1097/mpa.0000000000001958
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Endoscopic Retrograde Cholangiopancreatography Did Not Increase the Incidence of Postprocedural Pancreatitis Compared With Elective Cases

Abstract: Objective The aim of this study was to identify the incidence of and risk factors for post–endoscopic retrograde cholangiopancreatography pancreatitis (PEP) after emergency endoscopic retrograde cholangiopancreatography (ERCP). Methods We performed a prospective multicenter observational study of 3914 patients who underwent ERCP. We compared the incidence of PEP after emergency and elective ERCP. Results A total of 3410 patients were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
0
4
1
Order By: Relevance
“…In the multicenter prospective study conducted by Nakai et al, 3410 patients underwent ERCP, of whom 800 underwent urgent and 2610 underwent elective procedures, and there was no significant difference in PEP incidence between the two groups. 12 The hypothesis that a history of ERCP would increase PEP risk by increasing secondary inflammation and making the second ERCP procedure more difficult was not supported by our study. In Freeman et al's study, the presence of a history of ERCP was not found to be significant.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…In the multicenter prospective study conducted by Nakai et al, 3410 patients underwent ERCP, of whom 800 underwent urgent and 2610 underwent elective procedures, and there was no significant difference in PEP incidence between the two groups. 12 The hypothesis that a history of ERCP would increase PEP risk by increasing secondary inflammation and making the second ERCP procedure more difficult was not supported by our study. In Freeman et al's study, the presence of a history of ERCP was not found to be significant.…”
Section: Discussioncontrasting
confidence: 63%
“…In a study by Nakai et al, there was no significant difference found between patients who underwent emergency and elective ERCP. 12 Similarly, Matsubara et al also did not find a significant difference between the two groups. 19 Having a history of previous ERCP was found to increase the risk of PEP by 3.367 times (95% CI: 2.01-5.65), consistent with the results of the study by Freeman et al 10 The presence of cholangitis was associated with 5.050 times (95% CI: 1.497-17.036) increased risk of PEP, which aligns with the statistically significant findings in the study by Mutneja et al 17 The occurrence of PEP was significantly associated with the odds ratio (OR) of precut sphincterotomy, with a value of 3.564 (95% CI: 1.566-8.114), as observed in our study.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…1). The basic characteristics of the included studies are listed in Table I (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). These studies were from China, Sweden, Japan, Korea, Greece, the USA and Germany, including case-control, prospective cohort and retrospective cohort studies.…”
Section: Basic Characteristics Of the Included Studiesmentioning
confidence: 99%